Reabilitação em edifícios e monumentos art déco – métodos de avaliação dos revestimentos de fachadas - Munduruca, Elianne Auxiliadora Moreira Borges (2013)
Facade rendering perform various functions in buildings and monuments including aesthetic features, durability and economic value. However, over the years, the works begin to suffer deterioration processes, either natural or caused by unsuccessful intervention actions that trigger the onset of problems in the building rendering works, impairing these functions. In the case of historical buildings and monuments, the situation is even worse, because of the lack of knowledge of materials and techniques employed in implementing them at the time of construction. Thus, this thesis aims to study the most suitable methods for the inspection of works on facades and monuments of historical value and, from this research, aims to adapt a simplified methodology for the assessment of pathological manifestations of renderings, especially in art deco construction style built in Goiânia. To achieve this goal, was designed a case study in the Clock Tower, an important art deco monument of the capital of the Brazilian state of Goiás, has been proposed the following methodology: visual inspection for research and mapping of pathological manifestations present at the monument; photographic documentation; essay by percussion, to assess the state of rendering adhesion; application of the infrared thermograph technique; and also testing by pendulum sclerometry to evaluate the surface hardness of the rendering. As a result, it was found that the monument is deteriorated with the presence of various defects in the rendering, especially with a high cracking and dirt stains, and rust stains and disintegration. The south and north views of the tower are those most committed while in the west and east views, especially in the latter, the rendering is still in good condition.